2008
DOI: 10.4319/lo.2008.53.1.0014
|View full text |Cite
|
Sign up to set email alerts
|

High abundance and dark CO2 fixation of chemolithoautotrophic prokaryotes in anoxic waters of the Baltic Sea

Abstract: We determined the abundance and distribution of chemolithoautotrophic prokaryotes in the redoxcline in two basins (Gotland Deep, Landsort Deep) of the central Baltic Sea by combining dark CO 2 fixation measurements with flow cytometric cell sorting. Maximum CO 2 fixation rates were recorded in sulfidic waters about 20 m below the chemocline. Flow cytometric analyses of deoxyribonucleic acid (DNA)-stained bacterioplankton revealed the existence of at least five different prokaryotic clusters in water samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 35 publications
1
11
1
Order By: Relevance
“…During our observation period at Gotland Deep in 2007, 2008 and Landsort Deep in 2008, we found a characteristic water column stratification for the central Baltic Sea (Jost et al 2008, as exemplified for the Gotland Deep in 2007 in Fig. 1.…”
Section: Physico-chemical Characteristics Of the Central Baltic Sea Wsupporting
confidence: 51%
See 1 more Smart Citation
“…During our observation period at Gotland Deep in 2007, 2008 and Landsort Deep in 2008, we found a characteristic water column stratification for the central Baltic Sea (Jost et al 2008, as exemplified for the Gotland Deep in 2007 in Fig. 1.…”
Section: Physico-chemical Characteristics Of the Central Baltic Sea Wsupporting
confidence: 51%
“…In contrast to numerous detailed studies on the prokaryotic assemblages (e.g. Labrenz et al 2007, Jost et al 2008, Grote et al 2012, protist related studies of Baltic Sea redoxclines are limited to a few microscopy-based approaches (Setälä 1991, Detmer et al 1993) and one single 18S rRNA-based diversity study, covering 2 water depths of the Gotland Deep ). Two recent studies, which also provide data for different protist functional groups, focused on the role of protist grazing and viral lysis as prokaryotic mortality factors in the redox gradient (Anderson et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Later, stable isotopes showed that heterotrophic fauna generally do not consume these visually dominant foundation species (Fisher et al, 1994), which can comprise more than 90% of the community biomass (Govenar et al, 2005). Instead, the majority of vent-endemic fauna appear to feed on free-living microbes Breea Govenar (bgovenar@ric.edu (Menge and Sutherland, 1987 (Taylor et al, 2001), the Black Sea (Yilmaz et al, 2006), and the Baltic Sea (Jost et al, 2008). Active areas of research at hydrothermal vents are focused on the phylogenetic and physiological diversity of chemoautotrophic bacteria and archaea (e.g., Takai et al, 2006), the relative importance of different carbonfixation pathways in primary production (e.g., Hugler and Sievert, 2011), and the variation in diets among consumers.…”
mentioning
confidence: 99%
“…The number of bacterial cells in the enrichment culture was quantified using flow cytometry (FACS Calibur flow cytometer, Becton and Dickinson) as described by Jost et al (2008). Briefly, duplicate samples of 1 ml were taken weekly from the enrichment culture under stirred conditions and preserved with 100 µl paraformaldehyde.…”
Section: Cell Counting and Morphologymentioning
confidence: 99%